Impact of Climate Change on Snowmelt Erosion Risk - Jana Podhrázská; Jan Szturc; Josef Kučera; Filip Chuchma (Land)
Climate change affects all sectors of human activity. Agricultural management is influenced by changes in temperature and precipitation distribution both during the growing season and in the non-growing period. The contribution of snowmelt erosion to the total annual loss of arable soil has not yet been sufficiently emphasized. Based on the USLE principle, an equation for soil loss caused by snowmelt was derived, and the erosion potential of snow was determined for the conditions in the Czech Republic. In the foothill area of Větřkovice, an analysis of changes in selected climatic characteristics in the years 1961–2020 was elaborated. It was shown that the area is warming and the number of days with temperatures below 0 °C is decreasing. The total annual precipitation decreased by 18 mm. Furthermore, the erosion potential was compared in two referential periods for both the entire Czech Republic and the Větřkovice area, and a case study of soil loss due to snowmelt erosion was prepared. Despite a slight reduction in the erosion potential in the model area, the erosion shear from snowmelt reaches values higher than the permissible limit.